Association between self-care and prognosis in 1123 patients with chronic heart failure. (25th November 2020) - Calero, E; Hidalgo, E; Marin, R; Rosenfeld, L; Fernandez, I; Garay, A; Alcoberro, L; Jimenez, S; Yun, S; Guerrero, C; Moliner, P; Delso, C; et al.
Abstract: Background: Self-care is a crucial factor in the education of patients with heart failure (HF) and directly impacts in the progression of the disease. However, little is published about its major clinical implications as admission or mortality in patients with HF. Aims and methods: The aim of the study was to analyze time to admission due to acute heart failure and mortality associated with poor self-care in patients with chronic HF. We prospectively recruited consecutive patients with stable chronic HF referred to a nurse-led HF programme. Selfcare was evaluated at baseline with the 9 item European Heart Failure Self-Care Behavior Scale. Scores were standardized and reversed from 0 (worst selfcare) to 100 (better self care). For the purpose of this study we analyzed the associations of worse self-care (defined as scores below the lower tertile of the scale) with demographic, disease-related (clinical) and psychosocial factors in all patients at baseline. Results: We included 1123 patients, mean age 72±11, 639 (60%) were male, mean LVEF 45±17 and 454 (40, 4%) were in NYHA class III or IV. Mean score of the 9-item ESCBE was 69±28. Score below 55 (lower tertile) defined impaired selfcare behaviour. Those patients with worse self-care had more ischaemic heart disease, more COPD, and they achieved less distance in the 6 minute walking test. Regarding psychosocial items patients in lower tertile of self-care needed a caregiver more frequently, they present more cognitive impairment, depressive symptoms and worse score in terms of health self-perception. Multivariate Cox Models showed that a score below 55 points in 9-item ESCBE was independently associated with higher readmission due to acute heart failure [HR 1.26 (1.02–1.57), p value=0.034] and with mortality [HR 1.24 CI95% (1.02–1.50), p value=0.028] Conclusion: Poor self-care measured with the modified 9-item ESCBE was associated with higher risk of admission due to acute decompensation and higher risk of mortality in patients with chronic heart failure. These results highlight the importance of assessing self-care and provide measures to improve them. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Hospital Univesitario de Bellvitge